A study on the influence of Authentic Leadership on psychological contract: Mediating roles of procedural justice and leader trust - Choi, Joonwon; Lee, Byungjoo (Korean Journal of Industrial and Organizational Psychology, 2014)
This study investigated the influence of authentic leadership on psychological contract. In addition, through mediation analysis, mediating roles of procedural justice and leader trust were examined. The data was collected from 180 employees working with several companies based in Korea. Furthermore, 162 responses were put into analysis after filtering out inappropriate responses. The results showed that authentic leadership has positive relationship with psychological contract, procedural justice, and leader trust. Additionally, both procedural justice and leader trust have positive relationship with psychological contract. Mediation analysis suggested significant mediating effects for both procedural justice and leader trust. Finally, based on the result of the analysis, implications, limitations and suggestions for future research were discussed.